ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMTIF SISWA PEREMPUAN KELAS XII IPS - Estetika, Mia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research begins with the problem of "What are the factors that influence the consumptive behavior of female students of class XII SMAN 1 Singkawang?" With the sub-problems in this study are (1) what are the internal factors in students to behave consumptively ?, (2) What are the external factors in students to behave consumptively? This study aims to determine the internal factors and external factors of students that influence students to consumptive behavior. The form of this research is descriptive research with qualitative approach. As for the sample data in this study are female students class XII IPS which amounted to 6 people and teachers of counseling. The age of the studied sample was 17-18 years with female gender and the method of determining the sample using purposive sampling technique. The method used in this research is descriptive method. Data were collected using interview and observation instruments. Based on the results of interviews and observations show that the dominant factors in the internal factors are personality, self-concept, and lifestyle, while the dominant factors in external factors are culture, social class, and reference groups.Â Keywords : Consumptive Behavior FactorsÂ